Um sobrevôo no "Caso Marie Curie": um experimento de antropologia, gênero e ciência - Pugliese, Gabriel (2007)
The present article aims to make a new reading of the "Marie Curie Case" under the sign of the event. The intention, thus, is to explore relations constituent of the controversy that if Nobel of 1903 unfolded in the prize, that she honoured the discovery of the radioactivity and radioactive elements. The starting point, for such taken over on a contract basis, will be the mediations between the relations of gender and the not-human beings mobilized in the laboratories. To leave of these mediations I describe the male/female difference of possibilities in also make-existing the Nature in relation to the power that the gender definition gives to ones in detriment of others, but as when make-existing the radioactivity consisted to "devir" that it made this relation to stutter, changing it of direction. "Marie Curie Case" it becomes non-separable two domains immediately: as much the involvement of the relations of gender in the scientific production, how much the involvement of science in the gender relations. This event resounds for anthropological and feminists approaches of science, thus, I place them in quarrel in the measure where the relations of being able had made me to respect the devir that the craft of the scientist put in scene: the radioactivity.